Contrasts of urban development in Bauru city (SP): slum and fortified enclaves in Jardim Nicéia - Krause, Anna B. P.; Goulart, Jefferson O. (Revista Nacional de Gerenciamento de Cidades, 2022)
The urban development of medium-sized cities in the interior of São Paulo state reproduced, to a large extent, the segregating logic of the Brazilian urbanization of large urban centers throughout the XX century. This paper analyzes the remarkable characteristics of the recent urbanization process in the city of Bauru (SP), relating them to the rise of precarious settlements in the form of the favela and the phenomenon of contemporary segregation in fortified enclaves. The object of analysis is the Jardim Nicéia slum, located between gated condominiums in the southern part of the city. The methodology used included a bibliographic review of theoretical and analytical references, research on demographic and socioeconomic data sources (IBGE, City Hall and municipal public agencies) and socio-spatial analysis of the area, in order to interpret how segregation is reproduced in this specific territorial area.